Extra Muros : sculptures en plein air. - Jardin des Plantes, Lille (Lille : [s.n.], 1984)
Arman ; César ; De Saint Phalle, Niki ; Penone, Giuseppe ; Arel, Dominique ; Bossut, Etienne ; Bouillon, François ; Brochard, Yves ; Darras, Claude ; Douret-D'Hour, Marie-Dominique ; Egana, Miguel ; Honegger, Gottfried ; Kerlidou, Gwenaël ; Lavier, Bertrand ; etc.
Extra Muros : sculptures en plein air, Jardin des Plantes, Lille, 23 juin - 31 aout 1984
boek